Analisis Harga Pokok Produksi Menggunakan Metode Full Costing Dalam Penetapan Harga Jual Pada UD Alhes Furniture - Zevilla Adpadena; Hudi Kurniawanto (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Indonesia’s economic growth is supported by the micro, small, and medium enterprises (MSMEs) sector, which contributes significantly to GDP and employment. UD Alhesa Furniture, a wooden furniture manufacturer, faces challenges in determining selling prices amid intense market competition. This study aims to analyze the calculation of the cost of goods manufactured (COGM) using the full costing method and its impact on selling price determination. The research employed a qualitative approach with descriptive analysis, based on primary data obtained through interviews and observations, as well as secondary data from related literature. The results indicate that the company’s current COGM calculation is relatively simple, considering only raw material costs and part of direct labor costs, without systematically allocating overhead costs. The application of the full costing method, which includes all production costs—both fixed and variable—provides a more accurate cost overview and serves as a rational basis for setting selling prices with a minimum profit margin of 25%. A significant gap was found between the actual selling price and the price based on the full costing method, with some products sold below the COGM, potentially causing losses. In conclusion, the implementation of the full costing method enables UD Alhesa Furniture to determine objective selling prices, minimize loss risks, and improve cost control accuracy